Studies for controlling human-induced vibration of the Pedro e Ines footbridge, Portugal. Part 2: Implementation of tuned mass dampers - Elsa Caetano (2010)
The construction in Portugal of a relatively long and slender footbridge prone to pedestrian-induced vertical and lateral vibrations motivated an extensive study for the design and implementation of a control system based on a set of lateral and vertical tuned mass dampers (TMDs) This paper discusses the strategy adopted in the design and assessment of the efficiency of this control system, pointing out particular problems with the lateral TMDs that suggest that the currently adopted design methodologies are non-conservative The research is based on a thorough experimental investigation of the footbridge's behaviour prior to implementation of the TMDs, the results of which are presented in the companion paper, and includes a full experimental characterisation of the implemented TMDs Results of more than one year of dynamic monitoring of the bridge are presented here; they generally indicate low levels of vibration and a reduced rate of activation of the TMDs